An expanded HIV response to optimise outcomes for exposed infants in Kasungu disrict, Malawi - Chavura, Elton Chimwemwe (My University, 2024)
Benefits of water, sanitation, and hygiene (WaSH) extend well beyond the risk of diarrhoea. They include reduction in the risk of malnutrition, helminth infections and disproportionate adverse effects due to suppressed immune systems. The study evaluated the potential contribution of WaSH towards three outcomes: diarrhoea, linear growth trajectory and disease progression among HIV-Exposed Infants (HEI). A quantitative cross-sectional study was conducted in Kasungu, Malawi. The first study participant was randomly selected. However, next, every study participant was selected in the order of every Kth interval (rounded to 3) until the final sample size of 293 was reached. The methodologies of systematic reviews were appraised using a Mixed Method Appraisal Tool (MMAT). Marital status (p = 0.021), level of education (p = 0.001) and employment (p = 0.024) had significant influence on diarrhoea. WaSH and co-trimoxazole together reduced diarrhoea episodes by up to 67% (IRR _ 0.33, 95% CI 0.24–0.46, p < 0.0001). No difference in mean height for age z- score (0.01, 95% CI-0.16 to 0.18) between children who had access to WaSH and those without it. Plasma Viral load (VL) was significantly higher among helminths-infected than the non-infected group (5.01 log10 vs. 3.41 log10, p < 0.001). CD4+ T-lymphocyte count values were not significantly different in the co-infection group relative to those with HIV- infection alone. Besides the on-going use of cotrimoxazole prophylaxis, improved WaSH among HEI could be a cost-effective and sustainable intervention for the prevention of diarrhoea and remedy for slowing down the progression of the sub-clinical disease to symptomatic AIDS; but has inconsistent effects on linear growth trajectory. Given the dreadful state of living conditions among most HEI, biomedical interventions alone though necessary, are insufficient and narrow in scope. An expanded WaSH/HIV response, to address exposed infants’ vulnerability, therefore, offers them a more pragmatic recourse.
Keywords: Water; sanitation and hygiene; Helminths; Cotrimoxazole